The Spatial Principal by the Tobacco Farmer at Kapencar Village on the lope of the Sindoro Mountain, Wonosobo - Subroto, T. Yoyok Wahyu (Pusat Studi Lingkungan Hidup Universitas Gadjah Mada, 2010)
The Javanese Architecture typologies dominated by by Kraton Arhitecture such as Joglo, Trajumas and Limasan, and the local village architecture such as Srotongan and Panggang-Pe. Those Javanese Architecture refer to the form of roof.Some phenomena in the village of Kapencar indicated that its spatial setting is very specific which suitable for the farmer of tobacco. The naturalistic inquiry is used in analyzing the data. The research resulted that the farmer at Kapencar village is divided into three classifications of farmer. Those are the rich farmer (priyayi), the poor/ labor farmer (buruh tani)and the craft farmer. Each of them has the uniqueness of spatial setting for both of their houses and environment. The uniqueness be applied for the three spatial setting typologies which is suitable for the classification of the farmer. The priority rooms of the priyayi farmer houses are the jogan and loteng/ pyan, the priority room of craftfarmer houses are the jogan, loteng and pyan meanwhile the priority room of the farm worker are the pawon as the communal space.